Pengaruh Teknologi Acceptence Dan Website Service Quality Terhadap Costumer E-Satisfaction Pada PT.Rackh Lintas Asia - Margolang, Faisal; Lubis, Tukimin (Universitas Muhammadiyah Metro, 2023)
This study analyzes the influence of technology acceptance and website service quality on customer e-satisfaction at PT. Rackh Across Asia. The research method used in this research is descriptive quantitative. Samples were taken using the slovin formula, and using a probability sampling technique, namely proportionate stratified random sampling. The results of using the slovin formula in this study the researchers took a sample of 113 consumers at PT.Rackh Lintas Asia. The analytical method used is multiple linear regression method using the SPSS program. The research results obtained a coefficient value of 0.631, where the T-count > T-table (8.998 > 1.6584) and a significant value of 0.000 is less than 0.05 meaning that Acceptance Technology has a positive and significant effect on Customer E-Satisfaction, so Ha1 is accepted. The coefficient value is 0.243, where the T-count > T-table (3.446 > 1.6584) and a significant value of 0.001 is less than 0.05, meaning that Website Service Quality has a positive and significant effect on Customer E-Satisfaction, so Ha2 is accepted. It is known that Fcount (93,607) > Ftable (3.08), and a significance value of 0.000 <0.05, it can be concluded that the third hypothesis is accepted, meaning that the Technology Acceptance Variable (X1) and Website Service Quality (X2) influence simultaneously (simultaneously) to Variable Customer E-Satisfaction (Y)